MPCs through COVID: Spending, saving and private transfers - Thomas F. Crossley; Paul Fisher; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2021)
MPCs were directly elicited from a representative sample of UK adults in July 2020 using receipt of a hypothetical unanticipated, one-time income payment. Reported MPCs are low, around 11% on average. They are higher, but still modest, for individuals in households with high current needs. These low MPCs may be a consequence of the prevailing economic un-certainty. Further, the fraction of respondents that report they would change their transfer payments to or from family and friends is almost as large as the fraction that report they would increase their spending. This means that targeting direct fiscal stimulus payments to high-MPC individuals could be partly undone, and that the aggregate MPC out of a stimulus payment need not equal the population-average MPC.
Keywords: D12; D14; E21; 330; spending; MPC; crowding out; COVID-19